EVALUATION OF GROWTH RATE AND CHLOROPHYLL CONTENT OF CABBAGE MICROGREENS UNDER DIFFERENT LED LIGHT SPECTRA - Rommy Andhika Laksono; Elsa Novyanti; Fawzi Muhammad BF; Nana Suryana Nasution; Anggun Pertiwi (UIN Sunan Gunung Djati Bandung, 2026)
Microgreens are high-value horticultural commodities that are increasingly in demand due to their rich nutritional content and short harvesting period. One of the critical factors in microgreen cultivation is lighting, particularly the use of LED technology, which enables spectral manipulation according to the physiological requirements of plants. However, plant responses to light spectra are variety-specific, necessitating a thorough evaluation of the interaction between cultivar and LED spectrum to achieve optimal results. This study aimed to investigate the interaction effects between cabbage cultivars (Brassica oleracea var. Capitata) and LED spectra on plant height growth rate and chlorophyll content in microgreens. The experiment was conducted using a factorial Completely Randomized Design (CRD) with two factors: cultivar (Talenta F1, Takada F1, Summer Autumn, and Scarlet) and LED spectrum (white, blue, red, and a red–blue combination at 80%:20%). A total of 16 treatments were applied, each replicated twice. Observed parameters included plant height growth rate (cm/day) and chlorophyll content (unit). Data were analyzed using ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) when significant differences were detected. The results revealed a significant interaction between cultivar and LED spectrum for both observed parameters. The red spectrum (s₃) exerted the greatest influence on plant height growth rate, with the highest values recorded in Talenta F1 (0.40 cm/day) and Scarlet (0.31 cm/day). Conversely, the red–blue combination (s₄) produced the highest chlorophyll content, particularly in Scarlet (49.15 units) and Talenta F1 (40.35 units), indicating the synergistic effectiveness of combined spectra in supporting photosynthetic pigment synthesis. The Summer Autumn cultivar exhibited a positive response to the blue spectrum, while Takada F1 demonstrated flexibility under both white and red–blue spectra. The coefficients of variation (CV) were 15.47% for growth and 14.29% for chlorophyll, reflecting moderate variability and representative data quality.